Models of church planting in North India - Robertson, Nicholas Andrew (Gurgaon, India Nicholas Andrew Robertson, 2007)
"This project sought to provide alternative models of church planting both to members of Assemblies of God World Missions (AGWM) serving in North India and the members of North India's Assemblies of God (AG) national church." -- Abstract.
Thesis (D. Min.)--Assemblies of God Theological Seminary
Includes bibliographical references.
Keywords: Missions -- India; Christianity -- India